(4+4)-imine cage compounds with nitrogen-rich cavities and tetrahedral geometry [data] - Tian, Ke; Wang, Xubin; Schuldt, Moritz P.; Elbert, Sven; Rominger, Frank; Mastalerz, Michael (Universität, 2023)
Organic imine cage compounds have found a variety of different applications in several fields in materials science. To design tailor-made cages for corresponding applications, synthetic approaches to cages with tunable functionalities, sizes and shapes have to be found. Here we report a series of cages with truncated cubic shape and tetrahedral geometry possessing nitrogen-rich cavities.
Im Titel steht der Ausdruck (4+4) in eckiger Klammer
Gesehen am 24.08.2023
Keywords: Forschungsdaten; Datenbank